Cities are hotspots for threatened species - Christopher D. Ives; Pia E. Lentini; Caragh G. Threlfall; Karen Ikin; Danielle F. Shanahan; Georgia E. Garrard; Sarah A. Bekessy; Richard A. Fuller; Laura Mumaw; Laura Rayner; Ross Rowe; Leonie E. Valentine; et al. (Global Ecology and Biogeography, 2016)
Aim Although urbanization impacts many species, there is little information on the patterns of occurrences of threatened species in urban relative to non‐urban areas. By assessing the extent of the distribution of threatened species across all A ustralian cities, we aim to investigate the currently under‐utilized opportunity that cities present for national biodiversity conservation. Location A ustralian mainland, T asmania and offshore islands. Methods Distributions of A ustralia's 1643 legally protected terrestrial species (hereafter ‘threatened species’) were compiled. We assessed the extent to which they overlapped with 99 cities (of more than 10,000 people), with all non‐urban areas, and with simulated ‘dummy’ cities which covered the same area and bioregion as the true cities but were non‐urban. We analysed differences between animals and plants, and examined variability within these groups using species accumulation modelling. Threatened species richness of true versus dummy cities was analysed using generalized linear mixed‐effects models. Results A ustralian cities support substantially more nationally threatened animal and plant species than all other non‐urban areas on a unit‐area basis. Thirty per cent of threatened species were found to occur in cities. Distribution patterns differed between plants and animals: individual threatened plant species were generally found in fewer cities than threatened animal species, yet plants were more likely to have a greater proportion of their distribution in urban areas than animals. Individual cities tended to contain unique suites of threatened species, especially threatened plants. The analysis of true versus dummy cities demonstrated that, even after accounting for factors such as net primary productivity and distance to the coast, cities still consistently supported a greater number of threatened species. Main conclusions This research highlights that A ustralian cities are important for the conservation of threatened species, and that the species assemblages of individual cities are relatively distinct. National conservation policy should recognize that cities play an integral role when planning for and managing threatened species.